Parametric Type‐II Dirac Photonic Lattices. Issue 7 (25th May 2020) - Jin, Kaichao; Zhong, Hua; Li, Yongdong; Ye, Fangwei; Zhang, Yanpeng; Li, Fuli; Liu, Chunliang; Zhang, Yiqi
Abstract: Different from the Fermi surface of the type‐I Dirac semimetal being a point, that of the type‐II Dirac semimetal is a pair of crossing lines because the Dirac cone is tilted with open and hyperbolic isofrequency contours. As an optical analogy, type‐II Dirac photonic lattices have been also designed. Here, type‐II Dirac cones are reported in Lieb‐like photonic lattices composed of identical waveguide channels, and the anisotropy of the band structure is due to neither the refractive index change nor the environment, but only the spatial symmetry of the lattice; therefore, the proposal is advantageous and benefits experimental observation. Conical diffractions and Klein tunneling in the parametric type‐II photonic lattice are investigated in detail. The results provide a simple and experimentally feasible platform to study two‐dimensional topological photonic and other nonrelativistic phenomena around type‐II Dirac cones. Abstract : Type‐II Dirac photonic lattices composed of identical sites are reported, and the anisotropy of the band structure is due to neither the refractive index change nor the environment of the lattice, but only the spatial profile of the lattice. Conical diffraction and nonrelativistic quantum phenomenon (e.g., Klein tunneling) in the type‐II photonic lattice are investigated numerically.